Mimicking the Biology of Engineered Protein and mRNA Nanoparticle Delivery Using a Versatile Microfluidic Platform - Valentina Palacio-Castañeda; Rik Oude Egberink; Arbaaz Sait; Lea Andrée; Benedetta Maria Sala; Negar Hassani Besheli; Egbert Oosterwijk; Johan Nilvebrant; Sander C. G. Leeuwenburgh; Roland Brock; Wouter P. R. Verdurmen (MDPI AG, 2021)
To investigate the delivery of next-generation macromolecular drugs, such as engineered proteins and mRNA-containing nanoparticles, there is an increasing push towards the use of physiologically relevant disease models that incorporate human cells and do not face ethical dilemmas associated with animal use. Here, we illustrate the versatility and ease of use of a microfluidic platform for studying drug delivery using high-resolution microscopy in 3D. Using this microfluidic platform, we successfully demonstrate the specific targeting of carbonic anhydrase IX (CAIX) on cells overexpressing the protein in a tumor-mimicking chip system using affibodies, with CAIX-negative cells and non-binding affibodies as controls. Furthermore, we demonstrate this system's feasibility for testing mRNA-containing biomaterials designed to regenerate bone defects. To this end, peptide- and lipid-based mRNA formulations were successfully mixed with colloidal gelatin in microfluidic devices, while translational activity was studied by the expression of a green fluorescent protein. This microfluidic platform enables the testing of mRNA delivery from colloidal biomaterials of relatively high densities, which represents a first important step towards a bone-on-a-chip platform. Collectively, by illustrating the ease of adaptation of our microfluidic platform towards use in distinct applications, we show that our microfluidic chip represents a powerful and flexible way to investigate drug delivery in 3D disease-mimicking culture systems that recapitulate key parameters associated with in vivo drug application.